The Needs of Training to Improve Teacher Competence in Preparing Society 5.0 - Yulianto, Yulianto (Technium Social Sciences Journal, 2021)
Society 5.0 is a society that can solve various social challenges and problems by utilising various innovations that were born in the era of the Industrial Revolution 4.0 such as the Internet on Things (internet for everything), Artificial Intelligence, Big Data, and robots to improve the quality of human life. In facing the era of society 5.0, the world of education plays an important role in improving the quality of human resources. To face this era of Society 5.0, the educational unit also needs a change in the educational paradigm. Among them, educators minimise their role as learning material providers, educators become an inspiration for the growth of student creativity. This research aims at answering the questions on how the implementation of training for teachers to prepare the community 5.0 is and what the obstacles encountered in applying the knowledge and skills gained from the training are. Research is also intended for asking question related to what efforts have been made so that teachers have the competencies needed in the era of the Industrial Revolution 4.0 to prepare the Society 5.0. It is a qualitative research with a case study approach. Semi structured interviews were applied to teachers and representative of Bogor District Education Office. The research proved that training in order to improve teacher competence to prepare community 5.0 is very urgent to be held, so that teachers can prepare their students well to become part of Society 5.0.